2023
DOI: 10.3390/healthcare11222963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutritional Status and Physical Fitness on Cognitive Domains among Older Adults: A Cross-Sectional Study

Carmen Boquete-Pumar,
Francisco Álvarez-Salvago,
Antonio Martínez-Amat
et al.

Abstract: Background: The health issues presented by the aging population can result in reduced muscle mass, poorer physical function, and cognitive impairment. The goal of this study was to determine how nutritional status and physical fitness relate to cognitive impairment in older adults. Methods: A cross-sectional descriptive and analytical study involving 100 participants was carried out to analyze the impact of nutritional status and physical fitness on cognitive impairment. Nutritional status was assessed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…However, no statistically significant difference in predicted muscle mass (kg) was observed. The SPPB results we observed are in line with other studies, such as a recent study that found a positive association between a higher MMSE score and a lower duration of 4 m walking and a higher HS load [58]. Regarding predicted muscle mass (kg), our finding is in contradiction with previous research suggesting an association between poorer muscle status and worsening cognition.…”
Section: Discussionsupporting
confidence: 70%
“…However, no statistically significant difference in predicted muscle mass (kg) was observed. The SPPB results we observed are in line with other studies, such as a recent study that found a positive association between a higher MMSE score and a lower duration of 4 m walking and a higher HS load [58]. Regarding predicted muscle mass (kg), our finding is in contradiction with previous research suggesting an association between poorer muscle status and worsening cognition.…”
Section: Discussionsupporting
confidence: 70%